Pragmatic Analysis Of Agreement And Disagreement Expressions In Hospitality Business Negotiations At Denpasar - Aryati, Kadek Feni; Ekasani, Kadek Ayu (Institut Pariwisata dan Bisnis Internasional, 2026)
This study aims to identify and analyze the pragmatic strategies employed in agreement and disagreement expressions during business negotiations within the hospitality sector in Denpasar. Utilizing the framework of pragmatic theory, specifically speech acts and implicature, this research explores how hospitality business practitioners in Denpasar effectively and politely convey agreement and disagreement in negotiation contexts. Data were collected through direct observation and recording of negotiation conversations involving various stakeholders in the hospitality business, such as hotel managers, suppliers, and travel agents. The findings indicate that the use of appropriate pragmatic strategies, including hedges, indirect statements, and consideration of cultural context, plays a significant role in negotiation success. This research offers valuable insights for hospitality professionals and English language learners to understand the nuances of cross-cultural business communication and enhance effective and polite negotiation skills.